New multicent linkage testers for centromere-linked genes and rearrangements in Neurospora - David D. Perkins (Fungal Genetics Reports, 1990)
A tester described in 1972 contained readily-scored markers near the centromeres of all seven linkage groups (Perkins, Neurospora Newsl. 19:33). That tester, now called multicent-1, was somewhat more laborious to score than alcoy (Perkins et al. 1969 Genetica 40:247-278) or its successor alcoy;csp-2 (Perkins and Björkman 1979 Neurospora Newsl. 26:9-10). multicent-1 had the advantage over alcoy of requiring no follow-up cross to distinguish alternatives, and it was somewhat more effective in detecting linkage of left-arm markers. Because alcoy itself contains three translocations, multicent-1 was more likely to identify the chromosomes involved in new centromere-linked translocations (Perkins and Barry 1977 Adv. Genet. 19:133-285).